Open-Label, phase 2 study of blinatumomab as second salvage therapy in adults with relapsed/refractory aggressive B-cell non-Hodgkin lymphoma. Issue 9 (28th July 2020) - Coyle, Luke; Morley, Nicholas J.; Rambaldi, Alessandro; Mason, Kylie D.; Verhoef, Gregor; Furness, Caroline L.; Zhang, Alicia; Jung, A. Scott; Cohan, David; Franklin, Janet L.
Abstract: The phase 2 portion of this open-label phase 2/3 study assessed the efficacy and safety of blinatumomab as second salvage for aggressive relapsed or refractory (r/r) aggressive B-cell non-Hodgkin lymphoma (B-NHL) following platinum-based first salvage chemotherapy. Forty-one patients with aggressive disease (32% relapsed; 68% refractory) enrolled and received stepwise blinatumomab (9–28–112 μg/day) in a 70-day cycle 1 and an optional 28-day cycle 2; 19 (46%) completed cycle 1 and 3 (7%) completed cycle 2. The overall response rate after 12 weeks was 37%, including 9 (22%) complete metabolic responses. Eight (20%) patients (all responders) subsequently received stem cell transplants. Grade ≥3 adverse events were reported in 29 (71%) patients. Grade 3 cytokine release syndrome occurred in one patient. Grade 3 neurologic events occurred in 10 (24%) patients; all resolved. Blinatumomab monotherapy appears effective as second salvage therapy in patients with r/r aggressive B-NHL. Trial registration: NCT02910063.